2019
DOI: 10.1021/acs.orglett.9b01093
|View full text |Cite
|
Sign up to set email alerts
|

Potassium tert-Butoxide-Mediated Condensation Cascade Reaction: Transition Metal-Free Synthesis of Multisubstituted Aryl Indoles and Benzofurans

Abstract: An efficient and facile method to synthesize valuable disubstituted 2-aryl indoles and benzofurans in good yields has been demonstrated, based on a tert-butoxide-mediated condensation reaction involving a vinyl sulfoxide intermediate. Products are obtained from N- or O-benzyl benzaldehydes using dimethyl sulfoxide as a carbon source. The methodology features a wide functional group tolerance and transition metal-free environment. Preliminary mechanistic studies suggest that the reaction involves a tandem aldol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 98 publications
2
6
0
Order By: Relevance
“…On the basis of the above experimental results and in combination with previous literature, [15–18] a reasonable reaction mechanism was proposed using benzaldehyde 1 a and indole 2 a as an example and outlined in Scheme 4. Initially, benzaldehyde 1 a reacted with DMSO under base conditions to give the styryl sulfoxide A through an aldol condensation reaction.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…On the basis of the above experimental results and in combination with previous literature, [15–18] a reasonable reaction mechanism was proposed using benzaldehyde 1 a and indole 2 a as an example and outlined in Scheme 4. Initially, benzaldehyde 1 a reacted with DMSO under base conditions to give the styryl sulfoxide A through an aldol condensation reaction.…”
Section: Resultssupporting
confidence: 57%
“…On the basis of the above experimental results and in combination with previous literature, [15][16][17][18] a reasonable reaction mechanism was proposed using benzaldehyde 1 a and indole 2 a as an example and outlined in…”
Section: Resultssupporting
confidence: 55%
“…[b] Isolated yield. Based on the above experimental results and combination with previous literature, [14] a reasonable reaction mechanism was proposed using benzaldehyde 1 a and methanol 2 a as an example and outlined in Scheme…”
Section: Resultsmentioning
confidence: 64%
“…Our preliminary experiments revealed that the commonly used procedures to generate anionic species from alkyl alkynyl ketones with the use of DABCO 6 or PPh Therefore, we have chosen an inexpensive and easy-to-handle potassium tert-butoxide/DMSO catalytic system ( pK a ∼ 32) 12 to activate the model ketone 1a. To our delight, when ketone 1a was treated with t-BuOK (10 mol%) in DMSO at room temperature for 120 min (Table 1, entry 1), the desired oxa-spirocyclopropane derivative 2a was obtained in 10% yield.…”
Section: Resultsmentioning
confidence: 99%